The proterozoic guanhães banded iron formations, southeastern border of the São Francisco Craton, Brazil: Evidence of detrital contamination - Barrote, V.; Rosiere, C.; Rolim, V.; Santos, J.; McNaughton, Neal (Universidade de Sao Paulo, 2017)
The Guanhães banded iron formation (BIF) bearing succession occurs as tectonic slices, juxtaposed to Archean TTG granite-gneissic basement rock, developed during the Neoproterozoic-Cambrian Brasiliano collage. The succession has a maximum depositional age of ~2.18 Ga, from detrital zircons in quartzite, and consists of quartzites, schists, BIFs, gneiss and amphibolite, all metamorphosed under amphibolite facies conditions. The Guanhães BIF shows HREE enrichment and consistent positive Eu anomaly (PAAS-normalized REE+Y). Two types of contamination were observed in the samples. The first is contamination by an exotic detrital component, which resulted in low Y/Ho ( < 30) and Pr/Yb (SN) ratios. Evidence of such contamination, combined with inferred stratigraphic stacking data, indicates that the Guanhães BIFs were deposited on a shallow marine environment. The second type of contamination resulted in higher Eu-anomalies, positive Ce-anomalies, and higher REE+Y concentrations, possibly due to the interaction between later magmatic fluids and the Guanhães BIF. A strong Cambrian event is recorded in zircon age data. The uncontaminated samples display REE+Y distribution similar to other Precambrian BIFs, particularly those from the Morro-Escuro Sequence and the Serra da Serpentina Group, without true Ce-anomalies and Y/Ho close to seawater values (45). Geochronological and geochemical data presented in this paper strongly suggest a correlation between the Guanhães supracrustal succession and the Serra da Serpentina and Serra de São José Groups.